2003
DOI: 10.3138/jcfs.34.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Female and Male Medical Students’ Exposure to Violence: Impact on Well Being and Perceived Capacity to Help Battered Women

Abstract: This paper contributes to the literature on domestic violence in several ways. First, the analysis explicitly models the endogeneity of the decision to leave. Second, the sample of abuse victims is nationally representative and includes both women who temporarily leave and women who never leave their abusers. Finally, the analyses test the prediction that the mere presence of shelters will decrease violence within intact relationships. While the results do not support this hypothesis, this may be due to the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…While prior work has shown that female medical students were more likely than their male counterparts to report prior IPV exposure, [ 18 ] this finding did not achieve statistical significance in our study. Interestingly, the school reporting the highest rates of IPV (Medicine) was also the group with the highest percentage of male students.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…While prior work has shown that female medical students were more likely than their male counterparts to report prior IPV exposure, [ 18 ] this finding did not achieve statistical significance in our study. Interestingly, the school reporting the highest rates of IPV (Medicine) was also the group with the highest percentage of male students.…”
Section: Discussioncontrasting
confidence: 97%
“…[ 11 , 14 ] Medical students with personal histories of violence express concern about their future efficacy in aiding patients who have had similar experiences. [ 18 ] Nonetheless, students who report histories of abuse favor IPV training. [ 19 ] In order to provide effective learner-centered curricula, educators need to understand the potential extent of IPV exposure among students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical schools need to have appropriate support mechanisms in place for victims and potential victims of IPV, and students should be given a list of local resources. According to Ambuel et al, [14] students need to be allowed to process their feelings and experiences within their academic spaces. There should be a safe environment that fosters open, respectful sharing of experiences and ideas, appropriate supervision, and encouragement of responsible selfcare including access to psychotherapy and support groups.…”
Section: Discussionmentioning
confidence: 99%
“…Broader institutional and policy changes should also be implemented in academic programmes to enable early detection and management. [14]…”
Section: Discussionmentioning
confidence: 99%